The Cystic Fibrosis Impact Questionnaire: qualitative development and cognitive evaluation of a new patient-reported outcome instrument to assess the life impacts of cystic fibrosis - Kelly P. McCarrier; Mariam Hassan; Paul Hodgkins; Ellison Suthoff; Lisa J. McGarry; Mona L. Martin (SpringerOpen, 2020)
Abstract Background Patients with cystic fibrosis (CF) experience significant disease burden, including progressive pulmonary decline and reduced survival. This multicenter qualitative study was conducted to develop a new patient-reported outcome (PRO) measure to assess the impact of CF on patients' quality of life: the Cystic Fibrosis Impact Questionnaire (CF-IQ). Semi-structured qualitative concept elicitation (CE) interviews with patients and caregivers documented CF-related symptoms, impacts, and treatment experiences. Coded interview data were considered alongside existing PROs, published literature, and expert opinion to develop an initial scale. Three rounds of cognitive interviews evaluated respondent comprehension and facilitated refinement of the CF-IQ. Results Adult (N = 20) and pediatric (N = 22) patients with CF and their parents/caregivers (N = 22) completed CE interviews at 7 US clinics. The sample included patients aged 6-58 years, 57% females, and represented a broad range of disease severity (forced expiratory volume in 1 s range: 22%-127% predicted). Interviews identified 59 unique CF-related impact concepts in domains, including activity limitations (physical, social, leisure), functional limitations (school, work), vulnerability/lack of control, emotional impact, treatment burden, and future outlook. Concept saturation was achieved, and a draft questionnaire was developed. Findings from the cognitive interviews (n = 18) confirmed that instructions, items, and response scales were relevant and clear, and interpreted as intended by patients. Conclusion The CF-IQ is a 40-item novel PRO scale assessing a comprehensive set of patient-relevant concepts to characterize the multifaceted nature of CF. Qualitative interview data support the content validity of the CF-IQ, which is currently undergoing additional psychometric evaluation in patients with CF.